Determination of the value of public library services in a globalized society - Pichová, Simona; Chlebounová, Denisa (Žilinská univerzita, 2017)
Globalization is not just an economic and political process but also a cultural one. Institutions that are undoubtedly an integral part of cultural events include public libraries. Libraries with their functions contribute to social equality and justice, enable every citizen to gain access regardless of age, nationality or social status. It serves as an important presenter of values for the development of a culturally educated individual. The value of libraries can be difficult to express and its calculation can not be based on standard costs, as is the case in a normal production enterprise, requires a special process. This difficult process is used to estimate prices based on individual library users' surveys. The benefits of public services provided by public libraries are attributed to the individual preferences and values of public library users. This article describes ways to determine the value of basic library services - book lending. The data for the calculations are based on the research of the Municipal Library in Prague, which takes place from 2012 until present. This research provides the largest survey of public libraries in the Czech Republic that helps public libraries to orient their activities and to adapt their decision-making activities in the field of finance. The article also describes changes to libraries in a globalized society.
Určení hodnoty veřejných knihoven v globalizované společnosti
Keywords: public library; benefit; measurement; veřejné knihovny; užitek; měření